2018
DOI: 10.13052/jge1904-4720.843
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis for Conversionof Conventional Vehicle into Plug-InHybrid Electric Vehicle

Abstract: Electrical vehicles (EVs) are gaining more attention due to its environmental friendly approach. However, growth is limited by consumer mindset and its high initial cost in developing countries. In a country like India, the majority of the vehicle running on the road are fossil fuel based and it does not comply with emission norms. Conversion of the conventional vehicle (CV) into the plug-in hybrid electric vehicle (PHEV) is promising option to reduce environmental impact of present vehicles running on the roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Meanwhile, the occurrence frequency of impact load is presumed relatively small, and for that consideration, the torque correction factor is taken as Kt=1.5. The minimum shaft diameter ds is calculated with (10) [30]:…”
Section: Rotor Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the occurrence frequency of impact load is presumed relatively small, and for that consideration, the torque correction factor is taken as Kt=1.5. The minimum shaft diameter ds is calculated with (10) [30]:…”
Section: Rotor Componentsmentioning
confidence: 99%
“…Recent studies related to retrofitting systems having electrical machine components include transportation systems, industrial machinery, and power generation systems. Several studies regarding retrofitting of transportation systems and industrial machinery are: hybrid retrofits in the power coupling arrangement, namely between the internal combustion engine and in-wheel motors without mechanical equipment but directly done by the vehicle, compared to conventional parallel hybrid electric vehicle [9], converting the combustion engine vehicle into the plug-in hybrid electric vehicle (EV) [10], upgrading gasoline cars to EV using the new powertrain [11], describing a method for transforming a vehicle's conventional drivetrain into an electrically based power unit [12], conducting a field experiment of an immobile retrofitted EV battery for grid balancing [13], suggesting to improve a shaft generator frequency converter to save fuel while operating a boat by connecting it to the primary switchboard [14], retrofitting the existing computer numerical control (CNC) machines to do modest manufacturing process by employing the Arduino platform [15], and improving the performance of a machine vision system of former tractors to make it possible to control tillage tools and enable real-time field operations [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that lower conversion budgets and sustainable operational gains can be an advantage, especially due to reductions in battery costs. 21 In another study conducted by Gujarathiet al, 22 which was stated that an efficient and sustainable personal transportation solution was provided by converting a diesel Tata Indica model car into a plug-in hybrid vehicle. Despite the fuel economy, strong torque, and lower emission rates of electric vehicles, increasing battery sizes are considered as a weight factor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since e-vehicles are ecologic and environment friendly, all countries worldwide have reoriented their policies toward electrification of their transport sectors that already suffer from greenhouse gas emissions. This has led to extensive research on topics related to the field of hybrid electric vehicles such as: the control of electric propulsion systems [1][2][3][4], energy management [5][6][7][8], power electronics [9], power train architecture [10], vehicle safety [11], intelligent vehicle control [12,13], HEV fuel optimization [14], and HEV machine design [15]. Currently, the latter research topic is among the greatest trends in the field of automotive engineering.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in HEV applications, power source operating points are set via power management algorithms. Equations ( 9) and (10) show, respectively, that each of the n power sources and traction motors shown in Figure 2 can be operated at n distinct operating points. It is worth noting that the number of operating points of a given power source or traction motor depends on the problem under study.…”
mentioning
confidence: 99%